Relawan Abdimas Dalam Percepatan Vaksinasi 1,2, dan Booster Covid-19 Bekerjasama Polrestabes Medan dan Institut Kesehatan Helvetia - Julina Br Sembiring; Dalimawaty Kadir; Endang Marianti (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Antenatal Care is one of the pillars of safe motherhood in an effort to reduce maternal and fetal morbidity and mortality. This care is designed to control the mother's pregnancy. WHO estimates that 500,000 pregnant women die from complications related to pregnancy. This figure explains that mothers who do not take advantage of Antenatal Care visits are at risk of not knowing the problems or diseases that accompany their pregnancy. There are factors that can affect Antenatal Care visits including the role of health workers and family support. Reducing maternal mortality is one of the eight goals formulated in the international commitments of the Millennium Development Goals (MDGs) for the long-term development of Indonesia's health from 2005 to 2025, the contents of which are to improve the health status of the community through increasing access to health services which include increasing life expectancy. UHH) from 69 years in 2013 to 73.7 years in 2025, decreasing the Infant Mortality Rate (IMR) from 32.3 in 2018 to 15.5 in 2025. In making this a success, the Indonesian government implements health service activities such as antenatal care that helps improve the quality of health for mothers pregnant.